Membangun Kontrol Diri Remaja Melalui Pendekatan Islam dan Neuroscience - Ragwan Mohsen Alaydrus (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2017)
Adolescents are often associated with high work in risk taking behavior. Neuroscience experts then proposed hypotheses that tend to be related to adolescent brain development, in the prefrontal cortex and limbic systems. Through fMRI-related scanning is the cognitive ability that plays a role in self-regulation and decisionmaking is still growing until late adolescence. That's how the limbic system is so sensitive to socio-emotional stimuli. Therefore adolescents need to be changed. For these things can reduce the tendency of adolescents to behave deviant. Along with that, Hujjatul Islam Al-Ghazali also mentions self control as a testament to the strength of one's character. Preventive measures have been taken to improve adolescent selfcontrol and prevention in risky behaviors through varioustrainings. Nevertheless, the outcomes of the existing training proved not to provide long-term pricing. Furthermore this article discusses the approach that can be done by parents and educators as a combination of Islamic perspectives and neuroscience findings in assisting adolescents develop self-control.Keywords: adolescent, Islamic parenting, neuroscience, self control, risk taking behavior